2014
DOI: 10.1155/2014/532327
|View full text |Cite
|
Sign up to set email alerts
|

Research on Static Triaxial Mechanical Properties of New CementSoil Reinforced with Polypropylene Fiber

Abstract: Through the laboratory test, the mechanical properties of cementsoil with adding desulfurization gypsum, fly ash, and polypropylene fiber were studied. Three different percentages (0%, 0.5%, and 1.0%) of polypropylene fiber were mixed into new cementsoil for which the cement content is 15% of the dry soil weight, the desulfurization gypsum content is 2% of the dry soil weight, and the fly ash content is 1.0% of the dry soil weight. The new cementsoil strength reinforced with polypropylene fiber was studied by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…Lately, there has been increased research interest in soil matrices reinforced with natural fibres, due to the fact that they are renewable, biodegradable, environmentally friendly and low-cost. It has been demonstrated that fibres can be considered as good earth reinforcement material 46 . A number of studies also showed improvement in properties of fibre reinforced soil blocks over the unreinforced blocks 1-3, 5, 10, 11, 14, 15, 22-24, 28-31, 36, 39, 43 .…”
Section: Introductionmentioning
confidence: 99%
“…Lately, there has been increased research interest in soil matrices reinforced with natural fibres, due to the fact that they are renewable, biodegradable, environmentally friendly and low-cost. It has been demonstrated that fibres can be considered as good earth reinforcement material 46 . A number of studies also showed improvement in properties of fibre reinforced soil blocks over the unreinforced blocks 1-3, 5, 10, 11, 14, 15, 22-24, 28-31, 36, 39, 43 .…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate the suitability of soil types for only one technique of earth construction. There were a number of soil samples in previous studies that could be recommended for two techniques of earth construction, such as soil samples used in studies [6,7,19,33,38,39,45,46,54,[71][72][73][74][75][76][77]. Other soil samples from the previous studies could be recommended to be used for three techniques of earth construction [44,45,49,51,58,59,63,73].…”
Section: Atterberg Limitsmentioning
confidence: 99%
“…As Tang et al [7] reported, the inclusion of polypropylene fiber into cement soil can not only enhance the compressive strength of cement soil but also improve the toughness of cement soil. Besides, Wang et al [8] also found that the polypropylene fiber-reinforced cement soil has a significant increase in strength compared with the cement soil without polypropylene fiber. At the same time, it is observed that the stress-strain curve of polypropylene fiber-reinforced cement soil has typical strain hardening characteristics and the principal stress difference increases with increase in fiber content [8].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Wang et al [8] also found that the polypropylene fiber-reinforced cement soil has a significant increase in strength compared with the cement soil without polypropylene fiber. At the same time, it is observed that the stress-strain curve of polypropylene fiber-reinforced cement soil has typical strain hardening characteristics and the principal stress difference increases with increase in fiber content [8]. What's more, the proper dosage of polypropylene fiber is helpful to enhance the compressive strength of cement soil after freezing-thawing cycles.…”
Section: Introductionmentioning
confidence: 99%